The Cost-Benefit Analysis of Digital Timestamping in Maritime Logistics : The Case of Aikatieto - Heikkilä, Jukka; Heikkilä, Marikka; Kc Deuja, Manju (Slovenia, 2025)
This study evaluates the costs and benefits of a digital timestamping service implemented in Finland for commercial maritime traffic. Using qualitative interviews and procurement document analysis, we examine its impact on various stakeholders, including ports, ship operators, and regulators. Our findings reveal that while the service's acquisition cost was relatively modest, the total cost across the stakeholder network was approximately ten times higher due to connected investments required to fully leverage the service. Benefits clustered around three primary areas: improved coordination among maritime stakeholders, enhanced data quality, and better system integration. Unforeseen consequences include a shift in balance between participants and ancillary actors. The study provides insights for cost-benefit analysis methodologies for public digital infrastructure investments by making positive network effects visible for multiple stakeholders.
38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings